The Effect of Convenience on Customer Loyality of PT. Pegadaian Malalayang Branch - Supit, Ayu Hariva Masye; Dyrgo, Hongky; Teneh, Farly (Formosa Journal of Applied Sciences, 2024)
The purpose of this study is to ascertain how convenience affects client loyalty. In addition to analyzing the relationship between the impact of convenience in physical branches and the impact of ease of service through digital platforms on customer loyalty at PT. Pegadaian Cabang Malalayang, the degree of convenience provided by the company influences the customer's decision to keep using the service. A questionnaire is used in this study's quantitative methodology to collect data. The findings indicate that Customer Loyalty (Y) is significantly impacted by the Convenience variable (X). Tests for validity and reliability make sure the tools are reliable and valid. Convenience has a significant positive coefficient, according to a basic linear regression study, indicating that raising those qualities will raise customer loyalty. At PT Pegadaian Cabang Malalayang, convenience has a major impact on customer loyalty. The results of the F and T tests corroborate this fact.